High-resolution clonal mapping of multi-organ metastasis in triple negative breast cancer. Issue 1 (December 2018) - Echeverria, Gloria; Powell, Emily; Seth, Sahil; Ge, Zhongqi; Carugo, Alessandro; Bristow, Christopher; Peoples, Michael; Robinson, Frederick; Qiu, Huan; Shao, Jiansu; Jeter-Jones, Sabrina; Zhang, Xiaomei; et al.
Abstract Most triple negative breast cancers (TNBCs) are aggressively metastatic with a high degree of intra-tumoral heterogeneity (ITH), but how ITH contributes to metastasis is unclear. Here, clonal dynamics during metastasis were studied in vivo using two patient-derived xenograft (PDX) models established from the treatment-naive primary breast tumors of TNBC patients diagnosed with synchronous metastasis. Genomic sequencing and high-complexity barcode-mediated clonal tracking reveal robust alterations in clonal architecture between primary tumors and corresponding metastases. Polyclonal seeding and maintenance of heterogeneous populations of low-abundance subclones is observed in each metastasis. However, lung, liver, and brain metastases are enriched for an identical population of high-abundance subclones, demonstrating that primary tumor clones harbor properties enabling them to seed and thrive in multiple organ sites. Further, clones that dominate multi-organ metastases share a genomic lineage. Thus, intrinsic properties of rare primary tumor subclones enable the seeding and colonization of metastases in secondary organs in these models. It is unclear how intra-tumoral heterogeneity contributes to metastasis. Here the authors study the clonal dynamics of triple negative breast cancer metastasis using patient derived xenografts and demonstrate that primary tumor clones harbor properties that support seeding and colonization of multiple organs.